2008
DOI: 10.1124/jpet.108.140368
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Fenofibrate, a Peroxisome Proliferator-Activated Receptor α Agonist, and Simvastatin, a 3-Hydroxy-3-methylglutaryl-Coenzyme A Reductase Inhibitor, on Experimental Traumatic Brain Injury

Abstract: We and others have demonstrated that fibrates [peroxisome proliferator-activated receptor (PPAR)␣ agonists] and statins (3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors) exerted neuroprotective and pleiotropic effects in experimental models of traumatic brain injury (TBI). Because the combination of statins and fibrates synergistically enhanced PPAR␣ activation, we hypothesized that the combination of both drugs may exert more important and/or prolonged beneficial effects in TBI than each alone. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Importantly, simvastatin activated PPARγ-dependent pathway in heart failure42 and cardiovascular disease43, for example, it attenuated cardiopulmonary-bypass-induced myocardial inflammatory injury by activating PPARγ44. Pharmalogical studies suggested combination therapy with PPARs agonist and simvastatin may have important therapeutic significance45.…”
mentioning
confidence: 99%
“…Importantly, simvastatin activated PPARγ-dependent pathway in heart failure42 and cardiovascular disease43, for example, it attenuated cardiopulmonary-bypass-induced myocardial inflammatory injury by activating PPARγ44. Pharmalogical studies suggested combination therapy with PPARs agonist and simvastatin may have important therapeutic significance45.…”
mentioning
confidence: 99%
“…16,18,19 In cultures of human BBB endothelia, lovastatin and simvastatin were shown to decrease the translocation of both albumin and sucrose, but not normal leukocytes. 20 Microglia (i.e., the resident immune cells of the brain) are implicated in the secretion of glutamate, reactive oxygen species, and other inflammatory mediators, which may exacerbate cerebral edema and secondary neuronal injury.…”
Section: Effects On Inflammation and Excitotoxicitymentioning
confidence: 99%
“…Finally, if treatment was delayed by 3 and 8 hours post-injury, benefit in neurologic function was only seen with the fibrate-statin combination. 19 Simvastatin and marrow stem cells have also been shown to improve the functional outcome of rats up to 90 days after experimental TBI, both when used as a monotherapy and synergistically when given sequentially. The synergistic effect may be mediated by increased delivery of marrow stem cells to the peri-contusional area by statin-induced angiogenesis, and subsequent activation and survival of marrow stem cells secondary to trophic factors released from the new blood vessels.…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fenofibrate showed antioxidant effects demonstrated by decrease of intracerebral markers of oxidative stress [36]. A study from the same group assessed a synergistical effect of a combination therapy with fenofibrate and simvastatin, a lipid-lowering drug [42]. The administration of these pharmacological compounds in combination after TBI exerted a more sustained neurological recovery than the monotherapies and might have important significance for the treatment of TBI [42].…”
Section: The Role Ppars In Central Nervous System Traumamentioning
confidence: 99%